Enhanced critical current density in MgB2 with Dy2O3 particle additions - Chen, Soo Kien; Shaari, Abdul Halim; Lim, Kean Pah; Mohd Aris, Mohd Faisal (Penerbit Universiti Kebangsaan Malaysia, 2008)
This paper reports on the effect of oxide particle Dy2O3 additions on the superconducting properties of MgB2. The polycrystalline samples were prepared by well mixing magnesium and boron elemental powders, followed by heat treatment for in situ reaction in inert gas environment. All the samples showed MgB2 as the main phase with MgO and DyB4 as impurities. Magnetization measurements showed that the superconducting transition temperature, Tc remained largely unchanged (37.5 – 38K) even for Dy2O3 additions up to 15.0 wt.%. However, the transition curve was broadened in samples with larger amount of additions. The best sample with only 0.5 wt.% Dy2O3 additions had a Jc of around a factor of 4 higher compared to the pure sample at 6K(1T). Tem imaging showed the distribution of nano precipitates of DyB4 and MgO within the grain which may improve the pinning leading to enhancement in critical current density, Jc.